Karakteristik glukosamin hidroklorida (HCl GlcN) dari kitin dan kepiting Chitosan Biru Kolam (Portunus pelagicus) - Fajar Syukron; Rahman Karnila; Bustari Hasan (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
Shell of blue swimming crabs is an potential source of glucosamine as their producttion is abundant and not yet economically utilized. In tis study glucosamin was extracted from chitin and chitosan of blue swimming crabs shells by HCl of various concentrations (33%, 35%, 37%), and the products obtained were evaluated for rendement, quality characteristics. The results indicated that the highest glucosamine rendement was obtained from chitin extracted with 33% HCl, but the best purity, Lod and melting point was produced from chitosan extracted by 35% HCl. Compared to standar, glucosamin purity, Lod and melting point extracted from t kitosan was slightly lower. The purity, moisture, Lod and melting point of glucosamin extracted from chitosan of blue swimming crabs shell as well as standart was 65,543%; 5,208%, 0,856%; 186°C; and 95%; 5,194%; 0,767; 190°C respectively.